2019
DOI: 10.3390/socsci8110308
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Women in Public Service Leadership: A Rapid Review

Abstract: Masculinist contours have legitimized male domination in Indonesia’s upper public service ranks. However, some women have managed to crack the glass ceiling. A systematic search was undertaken of seven academic databases and the Google Scholar search engine to identify facilitative features of women’s career advancement through Indonesia’s echelon ranks. Fourteen articles, representing nine studies, were identified. While policy initiatives exist to increase women’s representation and career advancement, studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 63 publications
0
18
0
1
Order By: Relevance
“…Women's engagement in productive work is more often known as routine, less visible and less valued than that of men (Nawaz and McLaren 2016). In nearly all societies, both patriarchy and women's engagement in homosociability afford men greater opportunities in leadership, professional specialisations, "clean work" and higher earning capacities (McLaren et al 2019;Mehta and Awasthi 2019). Reproductive work is mostly performed by women and it is usually non-monetised, hidden and discursively cast as not "real work" (Delaney and Macdonald 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Women's engagement in productive work is more often known as routine, less visible and less valued than that of men (Nawaz and McLaren 2016). In nearly all societies, both patriarchy and women's engagement in homosociability afford men greater opportunities in leadership, professional specialisations, "clean work" and higher earning capacities (McLaren et al 2019;Mehta and Awasthi 2019). Reproductive work is mostly performed by women and it is usually non-monetised, hidden and discursively cast as not "real work" (Delaney and Macdonald 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to the UNDP on Dzuhayatin (2020), the Women Empowerment Index's Indonesian ranking is 110th out of 188 nations. Because conventional male dominance has been mirrored in the practice of a crucial function, the selection of men to senior strategic roles is sometimes used, even though the country is regarded as the female characteristic "motherland" (McLaren, Star & Widianingsih, 2019). Threats surrounding women are often the misrecognition of their potential in the decision-making phase and the presence of 'Asian Ideals' to justify the existence of women in critical roles (Dzuhayatin & Edwards, 2010).…”
Section: Understanding the Glass Ceiling Phenomenon Among Women Leade...mentioning
confidence: 99%
“…This phenomenon has been proved by the World Bank in 2018 that Indonesian women have dealt with glass-ceiling (McLaren, Star & Widianingsih, 2019). Compared to the major power, for instance, the United States, the nation remains the status quo to place a woman in the top position, which shows a progressive movement to accept women leaders, for instance, vice-president.…”
Section: Understanding the Glass Ceiling Phenomenon Among Women Leade...mentioning
confidence: 99%
“…The quality of a local government public service can be measured by how well the organizers of government agencies carry out their duties and authority to the community and the level of community satisfaction with services provided by local and central governments. Service quality is also essential in implementing a public service in Indonesia (Hadian, 2017;Martani et al, 2014) A poor public service reputation is permanently attached to the reputation of the Indonesian government's public service providers; it can be concluded that local government public services are vital for the community, so measurement is needed to measure the quality of public services (McLaren et al, 2019;Winarna et al, 2021a). The practice of maladministration in government public services does not only lead to corruption and bribery, but this practice can hinder government investment and development, especially in the area of local government.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted to fill the research gap that arose from the limitations of previous research. Previous research has several limitations; the first is that many previous studies still test public services using theoretical studies and have not used empirical studies with observations using data (Aritonang, 2017;Ayu & Karyani, 2020;McLaren et al, 2019;Pratama, 2019). Then the limitations of the two previous studies that examined public services in Indonesia were still very limited in the number of local governments; previous studies only focused on several or one islands of local government in Indonesia.…”
Section: Introductionmentioning
confidence: 99%